APLIKASI BIOAKTIVATOR EM-4 DAN BOISCA DALAM PEMBUATAN PUPUK ORGANIK CAIR SEBAGAI PENGEMBANGAN LEMBAR KERJA MAHASISWA (LKM) BIOTEKNOLOGI LINGKUNGAN - Safitri, Wulan Indri Safitri Indri; Marhadi, Imam Mahadi; Wulandari, Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrack:The research was conducted to determine the effect of bio-activator EM-4 and Boisca in the manufacture of liquid organic fertilizer. This research was conducted from March to June 2015. The results are used for the development of LKM (StudentsWorksheet ) on the concept of environmental biotechnology. This study consisted of two phases: the manufacture of Liquid Organic Fertilizer and stage of development of LKM. Phase manufacture of Liquid Organic Fertilizer use research